2001
DOI: 10.1029/2000gl003742
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of optical aurora triggered by the solar wind negative pressure impulse (SI)

Abstract: Abstract.A geomagnetic negative sudden impulse (SI') occurred on 3 August 1997 in association with a sudden decrease of solar wind dynamic pressure. The discrete auroras observed by an all-sky TV imager at Zhongshan in Antarctica (magnetic latitude is-•74.5øS) suddenly enhanced their luminosity and moved poleward at the time of the SI'. Following the primary enhancement, three cycles of quasi-periodic luminosity pulsations were observed with periods of about 10-14 min and their average position drifted equator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 13 publications
(12 reference statements)
1
27
0
Order By: Relevance
“…The observation of auroral disturbances during sudden expansion of the magnetosphere is not uncommon. For example, Sato et al [2001] associate an optical auroral enhancement with a negative solar wind pressure impulse. Their results showed field line resonance, which resulted in upward and downward field‐aligned currents.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of auroral disturbances during sudden expansion of the magnetosphere is not uncommon. For example, Sato et al [2001] associate an optical auroral enhancement with a negative solar wind pressure impulse. Their results showed field line resonance, which resulted in upward and downward field‐aligned currents.…”
Section: Discussionmentioning
confidence: 99%
“…Liou et al (2006) investigated 13 sudden decreases of the dynamic pressure from Polar Ultraviolet Imager (UVI) and found that globally both the auroral luminosity as well as the average energy of precipitating electrons decrease as a response. They noted that the result is not in contradiction with Sato et al (2001) as in some cases local brightenings did occur also in the global UVI pictures. Liou et al (2006) speculated that the decrease of the global luminosity may be explained by an adiabatic expansion and reduction of the mirror ratio of the precipitating electrons, while possibly induction electric fields and Fermi acceleration effects would be the cause of the decreasing energy of the loss cone electrons.…”
Section: Introductionmentioning
confidence: 86%
“…Lukianova (2003) and Stauning and Troshichev (2008) found that for negative pressure steps the temporal evolution of the polar cap index (PCI) is consistent with transient convection vortices that divert ChapmanFerraro currents from the magnetopause to the polar cap ionosphere. In a case study, Sato et al (2001) found that the local auroral brightness as measured by an all-sky-camera can increase after a negative pressure impulse. Liou et al (2006) investigated 13 sudden decreases of the dynamic pressure from Polar Ultraviolet Imager (UVI) and found that globally both the auroral luminosity as well as the average energy of precipitating electrons decrease as a response.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of negative impulses should not be ignored. For example, Sato et al [16] firstly studied the responses of aurora activities to negative impulses and found that aurora activities enhanced dramatically during the presence of the negative impulse. They proposed that FLRs were excited by the negative impulses; the electrons were accelerated by the upstream field aligned current associated with the FLRs in the polar region, causing the intensification of the aurora activities.…”
Section: Introductionmentioning
confidence: 99%